Botany in Rasa'il Ikhwan al-Safa's Epistle 21 : an English translation and analysis in light of moden botany - Wan Munira binti Wan Sulong (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2011)
This study is about botany by the Ikhwan al-Safa', a prominent name in the history of Islamic philosophy and science during the 10th century A.D. in Basra. The purpose of this study was to translate the 21st Epistle of the Rasa´il Ikhwan al-Safa' on the types of plants, from Arabic to English. The text was then analyzed in light of modern botany to find out the similarities and discrepancies between botany in Islamic civilization and the contemporary world. The comparison was made in accordance to the themes chosen by the Ikhwan al-Safa' in the particular epistle. The findings revealed that the Ikhwan al-Safa' wrote about a variety of themes in botany, these include morphology, physiology, reproduction, nourishment and seasonal and environmental aspects in agriculture. The writing was a detailed account in plant morphology in which the Ikhwan described and elaborated the shapes, colours, tastes and scents (odours) of plants. In plant physiology, the facts given were different from modern botany; it showed the classical view of plant growth which they believed were dependent on the seven active forces that reside in plants. While in plants nourishment the Ikhwan already stressed the importance of water to plant growth, sharing a common view with modern botany that eighty to ninety percent of plants are water. Their views on the origin of species, which was wrongly oversimplified by contemporary scholars as pro-Darwinism, were clarified here. The Ikhwan's stance is obviously against Darwinism; they strongly believed that the origin of species is fixed and distinctive from the beginning of creation. Each kind of plant and animal species is beautifully and distinctively designed by Allah in a unique creation and never will a species come from a different species, unless by the ultimate will and wish of Allah SWT.